Brucella Downregulates Tumor Necrosis Factor-α to Promote Intracellular Survival via Omp25 Regulation of Different MicroRNAs in Porcine and Murine Macrophages - Luo, Xiaomao; Zhang, Xiujuan; Wu, Xingchen; Yang, Xuefeng; Han, Cong; Wang, Zhengyu; Du, Qian; Zhao, Xiaomin; Liu, Shan-Lu; Tong, Dewen; Huang, Yong (Frontiers in Immunology, 2018)
Brucella spp. impedes the production of pro-inflammatory cytokines by its outer membrane protein Omp25 in order to promote survival and immune evasion. However, how Omp25 regulates tumor necrosis factor (TNF-α) expression in different mammalian macrophages remains unclear. In this study, we investigated the potential mechanisms by which Omp25 regulates TNF-α expression, and found that Omp25-deficient mutant of B. suis exhibited an enhanced TNF-α expression compared with wild-type (WT) B. suis, whereas ectopic expression of Omp25 suppressed LPS-induced TNF-α production at both protein and mRNA levels in porcine alveolar macrophages (PAMs) and murine macrophage RAW264.7 cells. We observed that Omp25 protein as well as WT B. suis up-regulated miR-146a, -181a, -181b and -301a-3p and down-regulated TRAF6 and IRAK1 in both PAMs and RAW264.7 cells, but separately up-regulates miR-130a-3p in PAMs and miR-351-5p in RAW264.7. The up-regulation of miR-146a or miR-351-5p attenuated TNF-α transcription by targeting TRAF6 and IRAK1 at the 3’UTR, resulting in inhibition of NF-kB pathway, while up-regulation of miR-130a-3p, -181a or -301a-3p correlated temporally with decreased TNF-α by targeting its 3’UTR in PAMs or RAW264.7 cells. In contrast, inhibition of miR-130a-3p, -146a, -181a and -301a-3p attenuated the inhibitory effects of Omp25 on LPS-induced TNF-α in PAMs, while inhibition of miR-146a, -181a, -301a-3p and -351-5p attenuated the inhibitory effects of Omp25 in RAW264.7, resulting in an increased TNF-α production and decreased intracellular bacteria in both cells. Taken together, our results demonstrate that Brucella down-regulates TNF-α to promote intracellular survival via Omp25 regulation of different microRNAs in porcine and murine macrophages.